Caring for Women Who Have Experienced Female Genital Cutting. Issue 5 (September 2015) - Little, Cindy M.
<x xml:space="preserve">Abstract</x> Abstract Female genital cutting/mutilation (FGC/M) is a procedure that involves physically altering a woman's/girl's genitals for no health benefits. This is a practice that is deeply rooted in culture, religion, and social tradition primarily in some African and Middle East countries. It is performed by a midwife, barber, traditional healer with no surgical training, or a physician. The practice of FGC/M has been gaining increased attention as women from those countries have been migrating to the United States and Western Europe. The World Health Organization (WHO) has estimated that 125 million women worldwide have undergone FGC/M. The practice has serious short-term and long-term physical, obstetric, and psychological complications. It has been proposed by some healthcare professionals that physicians or other healthcare providers should perform the cutting because it would be done under more sanitary conditions that would reduce complications. However, the WHO and other organizations have condemned the practice by any medical professional. The FGC/M procedure is a human rights violation and has been banned by WHO and other organizations and governments. This article provides an overview of the current issues related to FGC/M and addresses important cultural considerations for nurses caring for women with FGC/M. Nurses are in a unique position to provide holistic, culturally competent care in a respectful, nonjudgmental atmosphere. Nurses have a role in educating women with FGC/M about the complications and care, as education is necessary in the challenge to eradicate the practice of FGC/M.